(-1/3)^2 - (2/5)^3 + (7/8)^0 =
(-1/3)^4 - (-5/3)^0 +(-1/3)^3 =
6^6*(8^0-4)^-6=
[(pierwiastek z 5)^4-5^3]/ 0,01^-2=
(18^-2 -12^-3)*36^3=
(2^3-2^2*5^3)*0,25^-4 =
[(1/5)^-3 - (1/3)^-4]^-1 =
5^2 - (-4)^3+(-6)^3+(-1)9 =
4^-10*(8^3-2^9) =
(3^7*3^-9)/3^-6 =
(2/3)^-2 - (4/3)^-1 =
(-2)^5 - (-6)^2 +(1)^14+(-12)^0=

2

Odpowiedzi

2009-10-15T21:07:43+02:00
(-1/3)^2 - (2/5)^3 + (7/8)^0 = 1/9 - 8/125 + 1 =125/1125 - 72/ 1125 + 1= 53/1125 + 1 = 1178/1125 =~ 1,05

(-1/3)^4 - (-5/3)^0 +(-1/3)^3 = 1/81 - 1 - 1/27 = 1/81 - 81/81 - 3/81=
- 83/81

6^6*(8^0-4)^-6= 46656 x (-3)^-6= 46656 x (-1/3)^6 = 46656 x (-1/729)
= - 64

[(pierwiastek z 5)^4-5^3]/ 0,01^-2= ??

(18^-2 -12^-3)*36^3=
Najlepsza Odpowiedź!
2009-10-15T23:12:56+02:00
(-1/3)^2 - (2/5)^3 + (7/8)^0 =- 28/15=1 całość i 13/15
(-1/3)^4 - (-5/3)^0 +(-1/3)^3 =- 2 całości i 1/3
6^6*(8^0-4)^-6=-150
[(pierwiastek z 5)^4-5^3]/ 0,01^-2=
(18^-2 -12^-3)*36^3=7096896
(2^3-2^2*5^3)*0,25^-4 =14.8
[(1/5)^-3 - (1/3)^-4]^-1 =-11/15
5^2 - (-4)^3+(-6)^3+(-1)9 =-5
4^-10*(8^3-2^9) =-240
(3^7*3^-9)/3^-6 =12
(2/3)^-2 - (4/3)^-1 =-8/3=2 całości i 2/3
(-2)^5 - (-6)^2 +(1)^14+(-12)^0=16